A Case Report of Histoplasma-Associated Empyema Treated With Intravenous Injection and Local Thoracic Irrigation of Amphotericin B Plus Medical Thoracoscopy - Ning Cui; Lijun Wang; Jingming Zhao (Frontiers Media S.A., 2022)
Cases of empyema associated with Histoplasma infection are rarely reported. Here, we discuss a case of Histoplasma-associated empyema successfully treated with amphotericin B intravenous and pleural infusion therapy and multiple medical thoracoscopies. A 57-year-old Chinese woman with preexisting diabetes mellitus and gastric cancer had massive left-sided pleural effusion diagnosed by chest computed tomography. Her pleural effusion was purulent through pleural catheter drainage, and the culture of the pleural fluid showed Escherichia coli and Streptococcus constellation. Histopathology of the thoracoscopic pleural biopsy after hexamine silver and PAS staining supported Histoplasma infection. The patient was treated with intravenous injection and local thoracic irrigation of amphotericin B and continuous oral administration of itraconazole. At the same time, the patient received thoracic cannulation, daily thoracic lavage and thoracoscopy for purulent and necrotic tissue removal three times during hospitalization. The patient's pleural effusion and necrotic tissue in the pleural cavity were significantly reduced in a short time, and the clinical symptoms were significantly improved. After discharge, the patient recovered well and had no obvious complications or sequelae. Intravenous injection and local thoracic irrigation of amphotericin B are safe and effective drug therapies to treat fungal-associated empyema such as Histoplasma. Medical thoracoscopy effectively shortens the recovery time of empyema, improving the prognosis and reducing complications.